2014
DOI: 10.1254/jphs.13r17cp
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Pharmacological Potential of Plant Flavonoids in the Catecholamine System

Abstract: Abstract. Flavonoids are biologically active polyphenolic compounds widely distributed in plants. Recent research has focused on high dietary intake of flavonoids because of their potential to reduce the risks of diseases such as cardiovascular diseases, diabetes, and cancers. We report here the effects of plant flavonoids on catecholamine signaling in cultured bovine adrenal medullary cells used as a model of central and peripheral sympathetic neurons. Daidzein (0.01 -1.0 mM), a soy isoflavone, stimulated 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…* Adjusted for age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), 50-64 and 65-85 years), race and ethnicity (Mexican American, other Hispanic, non-Hispanic White, non-Hispanic Black, other), education (less than 9th grade, 9-11th grade, high school/GED), cotinine level (,0·01 (LOD), 0·01-10 and .10 ng/ml), hepatitis B (positive serum hepatitis B surface antigen and core antibody, negative) and hepatitis C (positive serum hepatitis C antibody, negative), fibre intake (gm).…”
Section: Discussionmentioning
confidence: 99%
“…* Adjusted for age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), 50-64 and 65-85 years), race and ethnicity (Mexican American, other Hispanic, non-Hispanic White, non-Hispanic Black, other), education (less than 9th grade, 9-11th grade, high school/GED), cotinine level (,0·01 (LOD), 0·01-10 and .10 ng/ml), hepatitis B (positive serum hepatitis B surface antigen and core antibody, negative) and hepatitis C (positive serum hepatitis C antibody, negative), fibre intake (gm).…”
Section: Discussionmentioning
confidence: 99%
“…4,16 Chronic heart failure is reported to be associated with the activation of the sympathetic nervous system as manifested by increased circulating catecholamines. 4,17 Furthermore, the stress hormone adrenaline stimulates b 2 -adrenoceptors, an effect that in turn activates the Gs protein/cyclic AMP-dependent protein kinase and the b-arrestin-mediated signaling pathway, reduces the p53 level, and induces DNA damage.…”
Section: Pharmacological Significance Of the Inhibitory Effects Of Mamentioning
confidence: 99%
“…4,17 Furthermore, the stress hormone adrenaline stimulates b 2 -adrenoceptors, an effect that in turn activates the Gs protein/cyclic AMP-dependent protein kinase and the b-arrestin-mediated signaling pathway, reduces the p53 level, and induces DNA damage. 18 Our recent review 16 and studies reported that daidzein, a soy isoflavone, 19 nobiletin, a citrus polymethoxy flavones, 20 and ikarisoside A, a natural flavonol glycoside derived from plants of the genus Epimedium, 21 suppress the secretion and synthesis of catecholamines induced by ACh in cultured bovine adrenal medullary cells. The present findings would support the idea that matsufushi extract and its constituent SJ-2 suppress the induction of catecholamine system hyperactivity by strong stress or emotional Fig.…”
Section: Pharmacological Significance Of the Inhibitory Effects Of Mamentioning
confidence: 99%
“…In fact, these naturally-derived biologically active polyphenolic compounds are widely distributed in plants and relatively common in human diets. In the past decades, a series of in vitro and in vivo investigations showed that several structurally related flavonoids such as wogonin, luteolin, nobiletin and baicalein have multiple biological effects including anti-oxidant, anti-inflammatory, anti-viral, neuroprotective, anxiolytic, and anti-cancer activities [81][82][83]. Here we focused on the potential anti-leukemia effects of wogonin.…”
Section: Wogonin and Wogonosidementioning
confidence: 99%